Efficacy of Dormancy Breaking Methods in Indica Rice Varieties - KOTA JANAIAH,; K. KANT,; M. DADLANI, (Seed Research, 2026)
Freshly harvested seeds of 44 rice varieties were used to test the efficacy of eight dormancy breaking methods. Among all the eight dormancy breaking methods tried in the 19 strong dormant varieties, dry heat treatment was most effective and the effectiveness of the other treatments was optimal. In four varieties, Kanak, Malaviya Dhan 36, Swarna and Intan, having strong dormancy, none of the treatments could improve germination beyond 70%. In the weak dormancy group dry heat treatment was most effective followed by moist heat and GA, (100ppm and 500 ppm). HNO3 (0.1N) treatment improved germination significantly in all the varieties with weak dormancy except in cv. Kasturi. Similarly H₂O, and KNO, seed treatments were not able to improve germination in cvs Kasturi, Pusa 44 and Narendra 359.